Haematological studies of various indigenous and exotic breeds of goats and their F1 crosses in Nigeria - Amakiri, S.F. (1981)
The haematology of three breeds of goats, the Saanen (S), Red Sokoto (RS), the West African Dwarf (WAD) and their crosses with each other (RS x S; WAD x S and WAD x RS) were studied to establish baseline dat and to monitor the direction of transfer of blood parameters at the F1 genration level of crossing. No significant differences were observed in the values obtained for the different genotypic groups, and for all parameters, the values for the F1 generation were not significantly different from those of the parent breeds.